EXPERT ASSESSMENT OF JOURNALISTS’ PROFESSIONALLY IMPORTANT QUALITIES - Bakhvalova, Alina (PSYCHOLOGICAL JOURNAL, 2019)
The article discusses the personal aspect of journalists’ professional self–esteem, which includes professionally important qualities (PIQ) or core personal competencies. We used the structure of professional self-appraisal that was proposed by a famous scientist Rean A.A. He pointed two main aspects of professional self–appraisal: the personal aspect and the operational–activity one. The topic of journalists’ professional self–esteem is important, because journalists determine public views by their work. At the same time journalists’ professional work is determined by their core personal competencies and moral values. However, journalists’ PIQ have not studied yet, as we have revealed after analyzing a lot of scientific articles (there are only articles about journalists’ creativity or values, but not about professional self-appraisal especially based on A.A. Rean’s theory). Thus, expert assessment of main journalists’ PIQ, previously selected from the corresponding professiograms and psychograms, was performed. The assessment was designed in the form of semantic differential, where every quality could be assessed from 1 up to 5. As experts, we invited scientists from the Institute of Journalism of National Taras Shevchenko University of Kyiv with their professional experience from 4 to 27 years. The results were analyzed with different statistical methods including clustering. We identified two groups of PIQ, which, in fact, is the same two groups as were identified by Karpov: absolute and relative PIQ. The first group consists of properties that are necessary to perform activities at the normative level (the basic PIQ for a particular type of activity). The second group, or relative PIQ, allows achieving outstanding results in the professional work. Thereby, according to the performed expert assessment, the following journalists’ qualities were included into the group of absolute PIQ: moral qualities, objectivity, ability to work with sources, critical thinking, efficiency, professional knowledge, philological skills and etc. Also, the following qualities are the relative PIQ: ingenuity, adaptability, correctness, activity, good attention, leadership qualities, good memory, stress resistance and etc.